Inclusion of Subjects who are Obese in Drug Development: Current Status and Opportunities - Vaidyanathan, Jayabharathi; Fletcher, Elimika Pfuma; Ramamoorthy, Anuradha; Madabushi, Rajanikanth; Burckart, Gilbert J. (Journal of clinical pharmacology, 2023)
The prevalence of obesity has grown tremendously in recent years and this population has an increased risk of disease comorbidities. The presence of disease comorbidities requires treatment interventions and proper dosing guidelines. However, drug development programs often do not have adequate representation of individuals who are obese in clinical trials, leaving gaps in the understanding of treatment response leading to a lack of adequate individualization options. Based on a recent survey of approved drug product package inserts, very few approved products included specific dosing based on obesity, in both adults and pediatrics. Reasons for the limited information on patients who are obese may include the under‐reporting of information regarding such patients and a lack of clinical trial diversity in enrolling patient groups in whom obesity or obesity‐related comorbidities are more prevalent. An inadvertent impact of the practice of exclusion of subsets of patients with some comorbidities in clinical trials may play a role in the reduced enrollment of individuals who are obese. Recently, regulatory authorities have taken specific initiatives to promote clinical trial diversity, including engaging with stakeholders and publishing regulatory guidance. These guidance documents highlight the need to enroll diverse clinical trial populations and provide recommendations on concepts related to drug development for obese populations. Such efforts will help to address the gap in information regarding drug response and dosing in patients who are obese.